Trends in C-Reactive Protein testing: a retrospective cohort study in paediatric ambulatory care settings - Alkhmees, M; Van den Bruel, A; Hayward, G; Blanker, MH; Walker, AS; Holtman, G (BMJ Publishing Group, 2024)
Objectives This study aims to investigate CRP testing practices in paediatric ambulatory care across British primary care and accident and emergency (A&E) departments‎. Design, Setting, Participants: This retrospective cohort study included ‎children <18 years old having ≥1 CRP test at primary care or A&E departments in Oxfordshire between 2007-2021. Outcomes: We estimated the frequency and annual changes in CRP testing in both settings‎, and evaluated referral and admission patterns based on CRP levels: low (<20 mg/L), ‎intermediate, or high (≥80 mg/L). Results Over 15 years, 91,540 CRP tests were requested in 63,226 children, with 33,882 (53.6%) in ‎primary care and 29,344 (46.4%) in A&E. Both settings showed rising trends in test requests, ‎with average annual percentage change of 3.0% (95% CI 1.2 to 4.7) in primary care and ‎‎11.5% (95% CI 8.6 to 14.6) in A&E. The proportion of intermediate/high-test results remained ‎stable. In primary care, 50,709 (95.8%) of tests were <20 mg/L, with 99.0% of these children ‎managed at home. High and intermediate CRP values increased odds of referral versus low CRP ‎(Odds ‎ratio (OR) adjusted for age= 21.80; 95% CI 16.49 to 28.81 and 4.77; 3.78 to 6.02, ‎respectively). At A&E, 27,610 (71.5%) children had CRP <20 mg/L, of whom 42.5% were ‎admitted, while 3,776 (9.8%) had CRP ≥ 80 mg/L with 57.9% admission rate. High and ‎intermediate CRP values increased odds of admission versus low CRP‎ (OR adjusted for age= ‎‎1.90; 95% CI 1.78 to 2.04 and 1.39; 1.32 to 1.46, respectively). Conclusion: There are rising trends of ‎CRP test requests at paediatric ambulatory care settings, with no evidence of increases in proportion of intermediate/high-test results in primary care. Low CRP values at primary care were linked to children managed at home, while almost half of children with low CRP values at A&E were admitted to hospital.